Safety and Efficacy of the Supine Position with the Right Shoulder Raised versus the Left Lateral Position in Peroral Endoscopic Myotomy for Achalasia: A Large-Sample Retrospective Study. (22nd September 2022) - Wang, Nanjun; Chai, Ningli; Li, Longsong; Bi, Yawei; Liu, Shengzhen; Zhang, Wengang; Wang, Shasha; Linghu, Enqiang
Abstract : Background . The correct surgical position is very important in the treatment of peroral endoscopic myotomy (POEM) for achalasia, which can make the procedure safer and more efficient. Currently, there are two commonly used positions: the supine position with the right shoulder raised and the left lateral position. This study aims to evaluate the differences in the safety and efficacy of these two positions. Methods . We conducted a retrospective study of 702 patients with achalasia undergoing POEM from December 2010 to December 2020. These patients were divided into the supine position with the right shoulder raised group (n = 579 ) and the left lateral position group (n = 123 ). The efficacy of POEM and adverse events were analyzed. Results . The clinical characteristics were similar in both groups, and there were no significant differences between the two groups in the Eckardt score change, lower esophageal sphincter (LES) basal pressure or residual pressure after POEM (all p > 0.05 ). The mean operative time in the supine position with the right shoulder raised group was significantly shorter than that in the left lateral position group (43.5 min vs. 54.6 min, respectively, p < 0.001 ). In addition, the differences between the two groups in terms of gas-related complications, such as pneumoperitoneum, pneumomediastinum, and subcutaneous emphysema were statistically significant (all p < 0.05 ). Conclusions . The efficacy of POEM was comparable between the two groups. However, the supine position with the right shoulder raised significantly reduced the operative time and the rate of procedure-related adverse events, especially gas-related complications.